2000
DOI: 10.1002/(sici)1097-0290(20000305)67:5<585::aid-bit9>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A high-yielding, generic fed-batch cell culture process for production of recombinant antibodies

Abstract: A fed-batch cell culture process was developed that has general applicability to all evaluated Sp2/0 (n = 8) and NS0 (n = 1) antibody-producing cell lines. The two key elements of this generic process were a protein-free concentrated feed medium, and a robust, metabolically responsive feeding strategy based on the off-line measurement of glucose. The fed-batch process was shown to perform equivalently at the 15 L development scale and 750 L manufacturing scale. Compared to batch cultures, the fed-batch process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…Sauer et al, (2000) reported 7.9 fold increase in average final mAb concentration developed the fedbatch process based on post-feed glucose concentration. According to Sauer et al [13], different post-feed glucose concentration result in producing different final mAb product titer, which is in accordance with our findings. The viability dropped significantly from day 5 to day 6 for Run #5, in spite of the feeding performed on day 5, indicating that the cells have entered the death phase of the cell cycle.…”
Section: Fed-batch Runsmentioning
confidence: 86%
See 4 more Smart Citations
“…Sauer et al, (2000) reported 7.9 fold increase in average final mAb concentration developed the fedbatch process based on post-feed glucose concentration. According to Sauer et al [13], different post-feed glucose concentration result in producing different final mAb product titer, which is in accordance with our findings. The viability dropped significantly from day 5 to day 6 for Run #5, in spite of the feeding performed on day 5, indicating that the cells have entered the death phase of the cell cycle.…”
Section: Fed-batch Runsmentioning
confidence: 86%
“…Prior to cell counting, samples were diluted 2 to 10-fold with 0.4% trypan blue solution (GIBCO, USA) depending on the cell density. From the VCD measurement, IVCC was calculated in the same manner as described by Sauer et al [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations